2019
DOI: 10.1080/15548627.2019.1633863
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive autophagy in intestinal stem cells controls gut homeostasis

Abstract: We recently found that rerouting intracellular vesicle traffic by suppressing macroautophagy/autophagy or endocytosis genes drastically deregulates Drosophila intestinal stem cell (ISC) proliferation, leading to massive gut hyperplasia that has a negative impact upon lifespan. Beginning with the poorly characterized Snx (sorting nexin) genes, we surveyed a broad set of genes in the endocytosis-autophagy network and found that most of them have this effect. We then discovered that deregulated Egfr-Ras85D/Ras1mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Mating and SP also cause inflammation and decreased life span, and these changes were found to be reversed by feeding the mated females the drug mifepristone, ( Landis et al, 2015 ; Tower et al, 2017 ). Aging in Drosophila is reported to involve further ISC proliferation and mis-differentiation (“dysplasia”), regulated in part by oxidative stress, EGFR signaling, and the microbiome ( Zhang et al, 2019 ; Zwick et al, 2019 ; Morris and Jasper, 2021 ). Mifepristone was first used in Drosophila as an activating trigger for the Gene-Switch artificial transcription factor ( Osterwalder et al, 2001 ; Roman et al, 2001 ; Ford et al, 2007 ), however, the ability of mifepristone to reduce inflammation and increase life span in the mated female does not require the presence of Gene-Switch ( Landis et al, 2015 ; Tower et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mating and SP also cause inflammation and decreased life span, and these changes were found to be reversed by feeding the mated females the drug mifepristone, ( Landis et al, 2015 ; Tower et al, 2017 ). Aging in Drosophila is reported to involve further ISC proliferation and mis-differentiation (“dysplasia”), regulated in part by oxidative stress, EGFR signaling, and the microbiome ( Zhang et al, 2019 ; Zwick et al, 2019 ; Morris and Jasper, 2021 ). Mifepristone was first used in Drosophila as an activating trigger for the Gene-Switch artificial transcription factor ( Osterwalder et al, 2001 ; Roman et al, 2001 ; Ford et al, 2007 ), however, the ability of mifepristone to reduce inflammation and increase life span in the mated female does not require the presence of Gene-Switch ( Landis et al, 2015 ; Tower et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, under conditions of starvation or oxidative stress, autophagy can also provide nutrients and energy to established metastatic tumors. In this way, autophagy can paradoxically act as a cancer-promoting factor [20]. Tumor cells can reuse proteins and damaged organelles through autophagy, and therefore survive despite drug treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Tomato yellow leaf curlvirus has been proved to enter whitefly Bemisia tabaci midgut epithelial cells through receptor-mediated clathrin-dependent endocytosis [37]. Zhang et al [38] reported that inhibition of endocytosis induced the proliferation of Drosophila intestinal stem cells and massive gut hyperplasia, which further affected intestinal development and lifespan. In this study, endocytosis-associated genes were found to be targeted by 60 DEpiRNAs in the Am4 vs. Am5 comparison group including piR-ame-14055 and piR-ame-456655 and five DEpiRNAs in the Am5 vs. Am6 comparison group it was regulated by such as piR-ame-31653 and piR-ame-1173337, indicating that corresponding DEpiRNAs potentially regulated the endocytosis during the development of larval guts.…”
Section: Discussionmentioning
confidence: 99%